Formulation and nutritional evaluation of kepilor instant cereal (soybean sprout, plantain banana, and moringa leaves) as functional food for type 2 diabetes mellitus - Palupi, Fitria Dhenok; Hapsari, Indri; Wattiheluw, Muhammad Hasan (Poltekkes Kemenkes Aceh, 2026)
Background:Type 2 diabetes mellitus (T2DM) is a global health problem with a continuously increasing prevalence and is strongly influenced by dietary patterns, particularly high energy intake, excessive simple sugars, and low fiber intake, which contribute to elevated postprandial glycemic responses. Effective management requires low-glycemic, nutrient-dense dietary interventions; however, commonly consumed processed foods, including instant cereals, often have high glycemic impacts. Therefore, the development of functional foods based on local ingredients such as plantain banana, soybean, and moringa leaves offers a promising strategy to support glycemic controlObjectives: This study aimed to formulate and evaluate an instant cereal based on plantain banana flour, soybean sprout flour, and moringa leaf flour (kepilor) that meets the dietary requirements for diabetes mellitus.Methods: This study employed a Completely Randomized Design (CRD) with three levels of plantain flour substitution (20%, 30%, and 40%), each conducted in triplicate. The parameters analyzed included organoleptic properties, yield, energy values, nutrient compositions, and energy densities. Nutrient composition was determined using standard methods (gravimetric, dry ashing, micro-Kjeldahl, Soxhlet, and carbohydrate by difference). Organoleptic evaluation was conducted using a 9-point hedonic scale with 30 semi-trained panelists, and the best treatment was determined using an effectiveness index test with 10 other trained panelists. Data were analyzed using ANOVA or Kruskal-Wallis test with p < 0.05Results: The results showed that formulation variations did not significantly affect protein, fat, carbohydrate, and fiber contents (p>0.05), with values ranging from 5.57–5.65 g, 2.83–2.90 g, 17.92–18.12 g, and 0.21–0.29 g per serving, respectively. However, significant differences were observed in total energy (119.40–120.63 kcal), energy density (0.597–0.603 kcal/mL), and taste (p<0.05), with taste being the only sensory attribute significantly affected by formulation. The formulation containing 30% plantain banana flour (T2) was identified as the best treatment, providing 120.63 kcal per serving, 5.65 g protein, 2.90 g fat, 17.98 g carbohydrates, 0.29 g fiber, and an energy density of 0.603 kcal/mLConclusion: In conclusion, kepilor instant cereal has potential as a low-energy-density functional snack suitable for the dietary management of individuals with diabetes mellitus.